Assistance in the Preparation of Financial Strategic Plans at the Noor Arsy Foundation - Risna Wijayanti; Himmiyatul Amanah Jiwa Juwita (AIBPM Publisher, 2022)
The Foundation has an organ consisting of Trustees, Management, and Supervisors. The management of wealth and the implementation of foundation activities are carried out entirely by the Management. The foundation must periodically make an accountability report for the funds obtained from donors in detail related to the planned use of funds receipts and expenditure plans. The problem faced by the Foundation is how to obtain sustainable sources of funds used to finance the company's operational activities. As a result of this condition the Foundation cannot operate continuously. This problem is caused by 1) Lack of understanding of the Noor Arsy Foundation management regarding the preparation of the Foundation's financial strategic plan, so that the plan to obtain funding sources has not been well planned, 2) There is no good understanding of how to draw up a financial strategic plan to provide adequate financial information for sustainability. foundation, 3) Documentation of financial data information used to prepare financial strategic plans has not been well documented. Based on the problems above, it is very necessary to assist in the preparation of strategic financial plans to maintain the sustainability of the Foundation